Studi Empiris Tentang Pengaruh Kebutuhan Perusahaan Terhadap Pemeriksaan Akuntan Publik Di Jawa Tengah dan Implikasinya Terhadap Pengembangan Profesi Akuntan Publik - Nasir, Mohammad (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 1997)
This research is designed as an empirical research to investigate some factors influencing the manufacturing firms on the demand of public accountant services. These factors include the company size, the amount of company's debt, and the number of stocks owned by management.The measurement of company size include its total assets, equities, sales, and the number of emplofees. The measurement of total company's debt includes the percentage of company's capital structure as well as total debt (current and longterm liabilities) and total equity (total stocks and retained earnings). The measurement of the number of stocks owned by management include the number of stock holders of the company, the number of stockholder who actively participated in managing the firm, the percentage of the stocks owned by the member of management and nonmember of management of the firm.For the sake of the research, 110 samples of manufacturing firms in Central Java were taken by using strati fied random sampling. The samples were analyzed by regression method. The research finding revealed that the com pany size, the company's debt, and the number of stock owned by management significantly influenced the demand for external auditor services for the small, me diu ra, and large firms. The bigger the company size and the more company's debt, the greater the possibility of the firms required the audit services by public accountants.However, the more stocks owned by management, the less the possibility of the finns demand audited by public accountants.